ANALISIS PERILAKU MASYARAKAT DALAM MENERAPKAN PROTOKOL PENCEGAHAN TERKAIT COVID-19 DI KELURAHAN SUDIREJO MEDAN - Muhammad Adji Wibisono; Achmad Rifai; Arifah Devi Fitriani (Jurnal Kesmas Prima Indonesia, 2021)
COVID-19 is a disease caused by a new type of corona virus, namely Sars-CoV-2. The worsening of the corona virus outbreak requires the government to take a stance so that each individual applies health protocols. Based on data from the UPT Puskesmas Simpang Limun in Medan City, the accumulated number of covid patients from March to July 2020 recorded 21 positive people for Covid-19, 2 people died and 19 people recovered. This study aims to analyze people's behavior in applying health protocols related to Covid-19 in Sudirejo Village, Medan City. This qualitative research was conducted from August to September 2020. Data was collected by conducting interviews and documentation of 8 informants. Data were analyzed using interactive analysis by Miles and Huberman. The results showed that public knowledge in implementing health protocols was still low, people's attitudes were also negative, because they thought that Covid-19 was an issue, besides that there were still many people who had not implemented health protocols. Based on these results, it can be concluded that the application of health protocols is closely related to people's knowledge, attitudes and actions. Therefore it is advisable for the Covid-19 task force to post Covid-19 prevention education posters in each region with a design that attracts attention so that people who do not use social media can read from the poster so that the public can add insight into health protocols related to covid-19.